Study of the prices of sugar and alcohol and its influence on long-term public stocks volume in Brazil - Wolff, Laion (2013)
This main objective of the study is to analyze transmission process between the price of sugar and prices of alcohol (anhydrous and hydrated) and the influence of the volume of public stocks of sugar, from January 2006 to July 2011. Were used in the analysis, the unit root tests of Dickey-Fuller (ADF), and Kwaiatkowski, Phillips, Schmidt and Shin (KPSS), of Johansen co-integration method and Vector Auto-Regression with Error Correction (VEC). The results show that sugar prices and the prices of anhydrous and hydrated alcohol influence each other, and that the volume of public stocks of sugar does not influence the prices out, what was expected, due to the volume does not change the price and but government intervention. Overall, shocks to variables in the model are transmitted quickly to the variable and are of short duration, disappearing after the sixth month.